Encyclopedia of Agrochemicals 2002
DOI: 10.1002/047126363x.agr344
|View full text |Cite
|
Sign up to set email alerts
|

Flooded Soils

Abstract: The microbiology of flooded soils is characterized by a large functional diversity that is seen in the numerous microbial phenotypes that occur in this ecosystem. This functional diversity is mainly due to the many different ecological niches created by gradients between oxic‐anoxic and substrate‐rich—substrate‐poor zones in the soil. These gradients are created by the limitation of the O 2 transport from the atmosphere into the soil because of slow diffusion and microbial respiration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 279 publications
0
21
0
Order By: Relevance
“…Wetland rice field soil has distinct biogeochemical cycles and microbial communities from upland soils (Conrad and Frenzel 2002;Kirk 2004), and rice roots growing in a submerged soil give the specific habitat for microorganisms through supply of oxygen and organic matter to the rhizosphere depending on the growth stage (Gotō & Tai, 1956;Andal et al 1956). The rice roots in the early growth-stage release oxygen to the surrounding soil making the rhizosphere oxic (Gotō and Tai 1956;Joshi et al 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wetland rice field soil has distinct biogeochemical cycles and microbial communities from upland soils (Conrad and Frenzel 2002;Kirk 2004), and rice roots growing in a submerged soil give the specific habitat for microorganisms through supply of oxygen and organic matter to the rhizosphere depending on the growth stage (Gotō & Tai, 1956;Andal et al 1956). The rice roots in the early growth-stage release oxygen to the surrounding soil making the rhizosphere oxic (Gotō and Tai 1956;Joshi et al 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The rice roots in the early growth-stage release oxygen to the surrounding soil making the rhizosphere oxic (Gotō and Tai 1956;Joshi et al 1973). The rice rhizosphere becomes anoxic when roots grow older due to the enhanced microbial activities on the released organic substrates and sloughed-off cells over the oxygen supply (Conrad and Frenzel 2002). Kimura et al (1979) showed that the rice roots have specific rhizosphere effect on both aerobic and anaerobic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the electrons from substrate oxidation flow into methanogenesis as predominant terminal reduction processes in rice paddies; however, iron oxide reduction is the second most important electron sink (Yao et al, 1999). Conceptually, iron oxide reduction occurs directly after flooding of rice field soil, and at interfaces such as water-soil and the rhizosphere, in which oxygen diffusion fuels the re-oxidation of iron(II) in steep chemical gradients (Conrad and Frenzel, 2002;Conrad, 2007). After flooding, oxidants (oxygen4nitrate4sulfate and iron(III) oxides) are reduced sequentially according to the thermodynamic theory (Ponnamperuma, 1972;Patrick and Reddy, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Methanogenic archaea are characteristic members of the microbial communities of anoxic wetland soils, e.g. flooded rice fields, where they are found in high abundance and diversity (Conrad and Frenzel, 2002). However, low numbers of culturable methanogenic archaea have also been found in oxic upland soils (Peters and Conrad, 1995; Küsel et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%